Analisis Penggunaan Tutorial Webinar di Masa Pandemi Covid-19 dengan Pendekatan Technology Acceptance Model Pada Universitas Terbuka - Binti Muflikah; Vica Ananta Kusuma; Swidarto Swidarto (Kelola: Jurnal Manajemen Pendidikan, 2022)
This study aims to analyze the acceptance of Universitas Terbuka Tutors for the use of the Microsoft Teams application and the Learning Management System (LMS) for Webinar Tutorials (Tuweb) during the Covid-19 pandemic. The method used in this research is explanatory. The population of this research is 416 tutors of UPBJJ Semarang Open University, while the research sample is 233 tutors in teaching group of Rembang, Blora, Pati, Kudus, Jepara, Demak, and Semarang. Research data was obtained from questionnaires, interviews, and documentation. Descriptive quantitative was used to analyze the data. The finding shows the acceptance of Universitas Terbuka Tutors in the use of the Microsoft Teams application for Tuweb obtained an average of 89.77 in the totally acceptable category with a contribution of 67.5%. In addition, the acceptance of tutors in using the LMS application obtained an average of 88.04 in the category of totally acceptable with a contribution of 75.0% from other dimensions. The conclusion was that the tutors accepted the Microsoft Teams and LMS applications. Therefore, they can be implied for Tuweb activities at UPBJJT UT Semarang.